Preparation and characterization of polysulfone membrane for gas separation - Jusoh, N. (Trans Tech Publications Ltd, 2014)
Symmetric and asymmetric polysulfone membranes were fabricated using different of solvents; N-methyl-pyrrolidone (NMP), Tetrahydrofuran (THF) and Dimethylacetamide (DMAC) at different polymer concentration (15 and 20) to study the influence of varying type of solvents and polymer concentration in membrane fabrication. The membranes were characterized using Field Emission Scanning Electron Microscopy (FESEM), Thermogravimetric Analyzer (TGA), Universal Testing Machine (UTM) and Fourier Transform Infra-Red (FTIR).The results disclosed that the symmetric, higher polymer concentration membrane contributed to better thermal and mechanical stabilities. PSF/THF membrane showed good mechanical strength while PSF/DMAC membrane illustrated great thermal stability. 20 of polymer concentration and PSF/THF membrane led to the thicker skin layer and dense structure formation. Â© (2014) Trans Tech Publications, Switzerland.